A simple simultaneous envelope/system optimization for energy efficiency improvement in near-zero energy buildings - Martín Muñoz-Salcedo; José L. Saquinaula-Brito; Jhonny Ortíz-Mata; Fernando Peci-López (Energy Conversion and Management: X)
This study develops a simple yet innovative framework for the simultaneous long-term optimization of building envelope strategies and energy systems in near-zero energy buildings (nZEB). The proposed framework evaluates the energy and economic performance of four envelope strategies—phase change materials (PCM), aerogel insulation, green walls, and awnings—integrated into a distributed generation mix comprising photovoltaic (PV) systems, wind turbines, battery storage, and grid support. The main objective is to analyze the influence of envelope solutions within the distributed generation mix to meet the building’s energy demand. The model is formulated as a mixed-integer disciplined convex program (MIDCP) and solved using the CVXR package in R, minimizing the total cost of envelope and energy systems over a 30-year period. The cost function is based on the CEN EN 15459 standard. Model validation is performed using real experimental data from a building located in Ecuador’s coastal region, characterized by a hot and humid climate. Its robustness is further verified through a sensitivity analysis that explores economic parameter variations and long-term climate change scenarios, combining EnergyPlus simulations with eplusr in R. Results indicate that the awning-based envelope strategy achieves the best performance under current conditions, with energy savings of 12–15 kW/year and a payback period of 8 years. For long-term economic viability, investment cost reductions of 73 %, 60 %, and 71 % are necessary for PCM, aerogel, and green wall solutions, respectively. This integrated optimization model provides a practical decision-making tool for evaluating cost-effectiveness and energy performance under evolving market and climate conditions.